Things Change: An Intergenerational Examination of the Correlates of Police Contact - Pollock, Wendi K. (Crime & delinquency, 2014)
From demographics, to technology, to attitudes, the U.S. population has changes since the 1970s. Over the past 40 years, policing has also changed to include more individuals who are female and non-White. Despite all of the changes, no study has yet been conducted to determine whether predictors of police contact, including factors such as race and gender, are consistent over time. The current study used multilevel Bernoulli models and logistic regression to examine two generations of respondents from the National Youth Survey Family Study. Results indicate some consistency in predictors of police contact between the two generations, with two notable exceptions: gender and socioeconomic status. Implications for police policy and practice are discussed.